Design and Implementation of a Web-Based Monthly Health Reporting System for the North Lampung District Health Office - Dilla Meilita; Ryan Aji Wijaya (Universitas Panca Marga, 2026)
The management of public health data at the district level still faces significant challenges, including manual reporting processes, data redundancy, and delayed information aggregation. These issues are also observed in the North Lampung District Health Office, where monthly health reports are still processed using fragmented and unintegrated systems. This study aims to design and implement a web-based monthly health reporting information system to improve data accuracy, integration, and reporting efficiency. The system was developed using the Rapid Application Development (RAD) method, which emphasizes iterative development and active user involvement. The system integrates health center data, disease classification (ICD-10), and LB1 morbidity reporting into a centralized platform equipped with real-time dashboards. Software evaluation was conducted using black-box testing and white-box testing, including cyclomatic complexity and code coverage analysis. The results indicate that all functional modules operate correctly, with code coverage exceeding 87% across all components. The system successfully reduces reporting time, improves data consistency, and enhances decision-making support for health authorities. Therefore, the proposed system provides an effective and reliable solution for digital transformation in regional health reporting systems.